Evolucija lesnih rastlin - Torelli, Niko (Les (Ljubljana), 1998)
Most important highliqhts of plant phylogeny with the special emphasys on the evolution of woody plants are presented. The gymnosperm and the cycadophyte-angiosperm lines of evolution can be traced back to the progymnosperms. Lycophytes represent a separate line of evolution that has been distinct since before the evolution of a cambium in the seed plant line. Cambium evolved independently in the different groups. The cambium and wood inmajor fossil plant groups is described.
Keywords: botanika; Rhododendron-Park Bremen; rastline; filogenija; evolucija; lesne rastline